Comparison of the early results of transforaminal lumbar interbody fusion and posterior lumbar interbody fusion in symptomatic lumbar instability - Sakeb, Najmus (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: Transforaminal lumbar interbody fusion (TLIF) has been preferred to posterior lumbar interbody fusion (PLIF) for different spinal disorders but there had been no study comparing their outcome in lumbar instability. A comparative retrospective analysis of the early results of TLIF and PLIF in symptomatic lumbar instability was conducted between 2005 and 2011. MATERIALS AND METHODS: Review of the records of 102 operated cases of lumbar instability with minimum 1 year followup was done. A total of 52 cases (11 men and 41 women, mean age 46 years SD 05.88, range 40-59 years) underwent PLIF and 50 cases (14 men and 36 women, mean age 49 years SD 06.88, range 40-59 years) underwent TLIF. The surgical time, duration of hospital stay, intraoperative blood loss were compared. Self-evaluated low back pain and leg pain status (using Visual Analog Score), disability outcome (using Oswestry disability questionnaire) was analyzed. Radiological structural restoration (e.g., disc height, foraminal height, lordotic angle, and slip reduction), stability (using Posner criteria), fusion (using Hackenberg criteria), and overall functional outcome (using MacNab's criteria) were compared. RESULTS: Pain, disability, neurology, and overall functional status were significantly improved in both groups but PLIF required more operative time and caused more blood loss. Postoperative hospital stay, structural restoration, stability, and fusion had no significant difference but neural complications were relatively more with PLIF. CONCLUSIONS: Both methods were effective in relieving symptoms, achieving structural restoration, stability, and fusion, but TLIF had been associated with shorter operative time, less blood loss, and lesser complication rates for which it can be preferred for symptomatic lumbar instability.